The great workplace how to build it, how to keep it, and why it matters - Burchell, Michael, 1967-; Robin, Jennifer, 1974-; ebrary, Inc.; Great Place to Work Institute (San Francisco : Jossey-Bass, 2011)
c
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Corporate culture; Work environment; Employee morale; Organizational behavior; Job satisfaction; Electronic books